Rediscovering the Delphi Technique: A Review of the Literature - Staykova, Milena P. (Advances in Social Sciences Research Journal, 2019)
The popularity of the Delphi technique as a research method has declined in the last decades. A review of the literature focusing on the technique presents a new and different opportunity for rediscovering the benefits of this type of research. Few recent studies have examined the process, reviewed the validity and reliability, and identified the appropriate sample size for the technique. In this paper, the author will include a review of the literature to discuss the pros and cons of using the Delphi technique in research.